Pengaruh Kualitas Pelayanan Dan Kelengkapan Produk Terhadap Minat Beli Konsumen Pada Toko Pelangi Kosmetik - Melani Milano Bombing Sulle; Dina Ramba; Lisa Kurniasari Wibisono (CV. Ulil Albab Corp, 2024)
The Influence of Service Quality and Product Completeness on Consumer Purchase Interest at the Pelangi Cosmetic Store. This research aims to determine the effect of service quality and product completeness on consumer buying interest at Pelangi Kosmetik stores. The data collection procedures for this research are: observation, questionnaires and documentation. The method used in this research is the Quantitative Method using the Multiple Linear Regression method and processed using SPSS 26. This research was conducted at the Pelangi cosmetics shop in Rantepao, with a sample size of 111 respondents. The technique that researchers used in sampling was accidental sampling. The results of calculations using the t test on the service quality variable t count > t table with a value of (20,020) > (2,361) and on the product completeness variable t count > t table with a value of (-10,737) < (2,361). The conclusion of this research is that service quality has a positive influence and has a significant influence on consumer buying interest. Product completeness has a negative influence and has an insignificant influence on consumer buying interest at the Pelangi cosmetics shop in Dirantepao